RELIGION AS ANTIDOTE TO HIV AND AIDS SCOURGE: A GLOBAL PERSPECTIVE WITH REFERENCE TO NIGERIA - Rotimi, Odudele (LIFE: International Journal of Health and Life-Sciences, 2015)
AIDS is still the most important new threat to human health globally and one of the serious problems Nigeria is battling with in this century. Recent years have seen a dramatic spread of HIV and AIDS from the initial focus in the country. Although our understanding of AIDS has increased, there have been little breakthroughs in the development of treatments and its eradication. This is because the rate at which this disease is killing active Nigerians, men, women and children alike is alarming. For instance, Nancy Snauwaert (2005) declared that 310,000 Nigerians died of HIV/AIDS related diseases in 2004 alone. It is obvious that the failure so far to check the spread of HIV/AIDS in the country only means that the prevailing strategy has not worked. In other words, too many Nigerians are still dying of the disease. As a result, there is need for more attention. The concern of the writer of this paper however, is that if all civil attempts of the government and non-governmental agencies fail to put an end into this evil vice, then the spiritual approach should provide an answer. This is what this paper tends to examine objectively.